Microbial Nano-Factories: Synthesis and Biomedical Applications - Ghosh, Shubhrima; Ahmad, Razi; Zeyaullah, Md.; Khare, Sunil Kumar (Frontiers in Chemistry, 2021)
In the recent times, nanomaterials have emerged in the field of biology, medicine, electronics, and agriculture due to their immense applications. Owing to their nanoscale sizes, they present large surface/volume ratio, characteristic structures, and similar dimensions to biomolecules resulting in unique properties for biomedical applications. The chemical and physical methods to synthesize nanoparticles have their own limitations which can be overcome using biological methods for the synthesis. Moreover, through the biogenic synthesis route, the usage of microorganisms has offered a reliable, sustainable, safe, and environmental friendly technique for nanosynthesis. Bacterial, algal, fungal, and yeast cells are known to transport metals from their environment and convert them to elemental nanoparticle forms which are either accumulated or secreted. Additionally, robust nanocarriers have also been developed using viruses. In order to prevent aggregation and promote stabilization of the nanoparticles, capping agents are often secreted during biosynthesis. Microbial nanoparticles find biomedical applications in rapid diagnostics, imaging, biopharmaceuticals, drug delivery systems, antimicrobials, biomaterials for tissue regeneration as well as biosensors. The major challenges in therapeutic applications of microbial nanoparticles include biocompatibility, bioavailability, stability, degradation in the gastro-intestinal tract, and immune response. Thus, the current review article is focused on the microbe-mediated synthesis of various nanoparticles, the different microbial strains explored for such synthesis along with their current and future biomedical applications.